Molecular mechanism of transcriptional activation of NR4A nuclear receptor subfamily - Yoo, Jun Yeob (Nanyang Technological University, 2022)
Diabetes Mellitus, a metabolic disease characterized by high blood sugar and other chronic symptoms, is a public health concern affecting more than 400 million people worldwide. Pathophysiology of diabetes is focused on the regulator hormone insulin, where Type 1 diabetes signifies autoimmune destruction of insulin-secreting cells, and Type 2 diabetes indicates other cases, including insulin resistance and dysfunctional insulin secretion. Although several medications have been introduced to the market, patients develop resistance to available treatments, and thus there is a pressing need to search for novel target proteins. Nor1 (also known as NR4A3) is a member of the orphan nuclear NR4A family. While earlier studies involving structural and molecular basis of ligand recognitions have been carried out on the other members of the NR4A family (NR4A1 and 4A2), the biological function of Nor1-ligand interaction remains largely unknown. Emerging evidence implicates that Nor1 plays a role in beta-cell signaling, where it is shown that Nor1 is involved in the direct expression of insulin peptide, the release of insulin vesicles, and survival of insulin-secreting beta cells. Thus, Nor1 is a suitable target for treating types of diabetes where the insulin secretion is impeded by cell death or dysfunctional insulin gene. This study presents the first solution structure of the Nor1 ligand-binding domain calculated by NMR spectroscopy, which is also the first NMR structure of any nuclear receptor ligand-binding domains. The Nor1-LBD NMR structures reveal a conserved structural portrait with other family members (NR4A1 and A2). This prompted us to screen potential naïve ligands and identify a novel endogenous molecule. Cell-based assays using insulin-secreting cell line were employed to characterize the role of Nor1 and the new ligand, demonstrating enhanced insulin secretion from pancreatic beta-cell through Nor1 signaling. The efficacy of this new ligand as an insulin secretagogue was comparable to market available T2D treatment drugs. These results corroborate that the structure of Nor1-LBD and its ligand-bound complexes could serve as a novel drug-discovery platform to develop anti-diabetic therapeutics.